Implementation Of AI Technology As An Innovative Learning Medium At SMK Dwijendra Denpasar: Training On Prompting And The Use Of AI-Based Media For Grade XI And XII Students - Ida Bagus Kresna Sudiatmika; Made Adi Paramartha Putra (Jurnal Pengabdian Mandiri, 2026)
The ability to utilize artificial intelligence (AI) technology is a crucial competency that young people must possess in the digital era. This community service activity aims to implement prompting training and the use of AI-based media for grade XI and XII students of SMK Dwijendra Denpasar from three departments: Computer and Network Engineering (TKJ), Accounting, and Hospitality. The implementation methods include interactive workshops, hands-on practice, and problem-based projects. A total of 87 students from the three departments actively participated in this program. The results show an increase in prompting ability by 93.7% and AI-based media usage ability by 130.0% after the training. Students also demonstrated significant improvement in confidence in using AI technology for learning and work purposes. This program proves that structured and contextual AI training is effective in improving the digital skills of SMK students across department.